The Satisfaction with the Health Care Service of Local Residents in Korea - Jeon, Misoon (International Journal of Psychosocial Rehabilitation, 2020)
Background/Objectives: This study was conducted to establish a health care plan to meet the health care needs of local residents and systematically execute various health care projects. Methods/Statistical analysis: Tools for measuring the satisfaction with the health care services of the subjects were revised and supplemented by the tools of the Community Health Survey. The data was collected from 423 local residents by structural questionnaire. Data was analyzed using SPSS 18.0. Findings: As a result of analyzing the number of annual use of public health center service, the total ’no use’ was 47.0%, and in area A, ’no use’ was 51.6% and area B was 40.3%. And the purpose of visiting health centers was the highest in the area of ’disease diagnosis and treatment’ (32.2%), followed by ’health promotion services’ (23.5%), ’other’ (21.3%), and ’flu vaccines’ (14.8%). The satisfaction level of the health care services was 3.37 points out of 4 points for vaccination, 3.29 points for health education, and 3.27 points for infants and maternal care. In terms of service satisfaction by health promotion project, no smoking was 3.43 out of 4 points, 3.31 points on exercise, 3.26 points on no alcohol, and 3.26 points on nutrition. Improvements/Applications: It will improve the self-management ability and quality of life of residents by establishing a health plan based on the data analyzing the satisfaction of health services of local residents.